Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$\int \frac{1}{\sqrt{x(1-x)}} dx $$ I solved the integral in this way: make the substitution $x=\sin^2(u)$, then $dx=2\sin(u)\cos(u)du$. So the integral now becomes $$\int \frac{2\sin(u)\cos(u)}{\sqrt{\sin^{2}(u)(1-\sin^{2}(u))}} du=\int 2 du=2u+C.$$ Then subbing in $u=\arcsin(\sqrt{x})$ I get the solution $$2\arcsin(\sqrt{x})+C.$$ However when I typed in this integral onto Wolfram it gave me this.

So my question is did I get it wrong or are the two forms equivalent?

share|cite|improve this question
These answers are equivalent for $0<x<1$. – Sasha Jan 29 '13 at 16:53
Note that the Wolfram answer requires complex numbers in this range. There is a connection between the complex logarithm and the inverse trigonometric functions derived from the similar connection between the complex exponential and the trigonometric functions that explains this phenomenon. – Harald Hanche-Olsen Jan 29 '13 at 16:54
FWIW, the graph of your solution matches the graph of the real part of the Wolfram solution – DJohnM Jan 29 '13 at 17:03
@Sasha totally forgot about the sqrt and the range of real values it could take and also the fact that Wolfram gives complex solutions. – SomethingWitty Jan 29 '13 at 17:05
up vote 4 down vote accepted

First of all, we never have to ask whether we got a correct antiderivative - because we can just take the derivative of our answer and see what we get: $$ \frac d{dx} \big( 2\sin^{-1}(\sqrt x) +C \big) = \frac2{\sqrt{1-(\sqrt x)^2}}\frac d{dx}\sqrt x = \frac2{\sqrt{1-x}} \frac1{2\sqrt x} = \frac1{\sqrt{x(1-x)}}. $$ So you did it right.

There's another way of finding the antiderivative: complete the square inside the square root to see that $$ \frac1{\sqrt{x(1-x)}} = \frac1{\sqrt{1/4 - (x-1/2)^2}} = \frac2{\sqrt{1-(2x-1)^2}}. $$ Therefore, using the substitution $u=2x-1$, \begin{align*} \int \frac1{\sqrt{x(1-x)}} \,dx = \int \frac2{\sqrt{1-(2x-1)^2}} \,dx &= \int \frac1{\sqrt{1-u^2}} \,du \\ &= \sin^{-1} u + C = \sin^{-1} (2x-1) + C. \end{align*} This can also be verified by differentiating.

(Side note: it's possible to check directly that $\sin^{-1}(2x-1)+\pi/2 = 2\sin^{-1}(\sqrt x)$, by taking the cosine of both sides, using $\cos(\theta+\pi/2) = -\sin\theta$ on the left and the double-angle formula $\cos 2\theta = 1-2\sin^2\theta$ on the right. Pretty cool!)

share|cite|improve this answer

Put $\displaystyle x = \frac{1}{2}+t$ and $dx = dt$

So $\displaystyle \int\frac{1}{\sqrt{x.(1-x)}}dx$ is converted into

$\displaystyle \int\frac{1}{\sqrt{\frac{1}{2^2}-t^2}}dt = \sin^{-1}(2t)+\mathbb{C} = \sin^{-1}\left(2x-1\right)+\mathbb{C}$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.